Dutch Translation and Validation of the Headache-Specific Locus of Control Scale (HSLC-DV). (2nd May 2018) - Willekens, Marceline C.; Postel, Don; Keesenberg, Martin D. M.; Lindeboom, Robert
Abstract : Background and Objective . The assessment of locus of control forms an important part of headache treatment, and there is need to adapting them to the Dutch population. Methods .Forward-backwardtranslation was used to obtain theHeadache-SpecificLocus of Control Scale–Dutch Version (HSLC-DV).The response of 87 participants with migraine, tension-typeheadache, and cervicogenic headache, aged between 18 and 55 years (75% female), is used.Test-retestreliability was measured by intraclass correlations. Construct validity was assessed by correlations with corresponding domains of the Pain Coping and Cognition List (PCCL) and by confirmation of known groups hypotheses. Structural validity was evaluated by factor analysis (principal axis factoring). Results . The intraclass correlations for the External, Internal, and Chance domains were 0.79, 0.89, and 0.73, respectively. Internal consistencies for domains exceeded 0.73 and were similar to those observed in the original study. Convergent correlations were as expected and three of the seven known groups hypotheses were confirmed. Structural validity was supported by results of the factor analysis that matched the proposed structure of the original instrument. Conclusions . TheHSLC-DVis a valid and reliable questionnaire for measuring the locus of control.